Paulo Orósio e o providencialismo no marco do Império Romano - Maria Sonsoles Guerras (Classica, Revista Brasileira de Estudos Clássicos, 1989)
This work makes part of the collective research of some professors and students of the History Department – Sector of Ancient and Medieval History – of UFRJ, who are financed by CNPq. Ater making a brief biographical sketch of Paulo Orósio, contemporary of Agostinho from Hipona, we analise the traces of the classical Roman culture that can be found in his work: the authors who served as sources for him, Cicero’s doctrine of classic historiography that he follows, and so on. The second part contains an analysis of some facts from Roman history which are, in the point of view of the author of the "Seven Books of History", a clear demonstration of how Providence has made use of the Roman World to start a new era: Christ is born during August’s time, therefore these two events will be forever joint and the "Pax Romana" will be the very beginning of the "Pax Christi". The objective of work is the analysis of Paulo Orósio's historical providentialism, for whom the Roman Empire is God’s Instrument for getting to the real Universal Christian Empire. according to Daniel’s prophecy.